Internalisasi Perutusan Kristiani Aktivis Orang Muda Katolik (OMK) di Paroki Keluarga Kudus Atmodirono Semarang: Studi Eksegetis dan Pastoral Matius 4:19 - Nerita Setiyaningtiya; Alexander Rexy Triatno; Yustinus Joko Wahyu Yuniarto (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2026)
This research examines the internalization of Jesus' commission in Matthew 4:19 by Catholic Youth Activists (OMK) at Holy Family Parish Atmodirono Semarang. Employing qualitative methodology and exegetical analysis, this study explores how young Catholic activists understand and implement Jesus' commission, their efforts to follow Him as disciples, and their integration of spiritual values into daily life. Data was collected from six informants through in-depth interviews, observation, and document analysis, then processed using thematic analysis. Findings reveal a spectrum of understanding regarding Jesus' commission—from basic interpretation to comprehensive understanding. Implementation manifests through liturgical and non-liturgical service, while discipleship efforts include strengthening prayer life, developing leadership skills, and adopting a gradual approach to ministry. Spiritual values are integrated through personal devotion, positive interpersonal relationships, and community participation. Despite challenges including limited human resources and social pressure, Catholic youth activists demonstrate creativity in contextualizing Jesus' commission in the digital era, including utilizing social media as an evangelization platform. This research contributes valuable insights on the spiritual dynamics of Catholic youth activists in interpreting and actualizing evangelical commission within contemporary Indonesian society.